Queue Model Analysis at PT Bank Rakyat Indonesia Manna Branch Office in South Bengkulu - Marike, Leriza; Abdillah, Willy (Universitas Bengkulu, 2024)
The purpose of this study was to describe the teller waiting list at the Bank Rakyat Indonesia Manna branch office in Bengkulu Selatan. This research is a type of qualitative descriptive research that explains how the application of the queuing system at the BRI bank teller Manna Branch Office in South Bengkulu. The data collection method of this study uses observation and the tool used to make observations is a stop watch which is used to measure how long it takes customers to make transactions at the teller and will be calculated using the B model: M / M / S (Multi-Channel Single Phas) model. Based on the results of the study, it shows that the service provided by the level of use of 3 teller facilities is still not optimal and the utility level is still low if the number of customers is above 173 per day. Therefore, based on the analysis, there must be an alternative done by the bank by adding 1 teller. And in quiet conditions or not busy days because it has a low level of facility usability and a low level of teller busyness, the author suggests that the BRI bank Manna Branch Office in South Bengkulu for tellers can be utilized for other work such as clearing administration and tax reports